Fibrolipoma of buccal mucosa - Monika Khubchandani; Nilima R Thosar; Rakesh N Bahadure; M S Baliga; Rahul N Gaikwad (Wolters Kluwer Medknow Publications, 2012)
The lipoma is a very common benign tumor of adipose tissue, but its presence in the oral and oropharyngeal region is relatively uncommon. Fibrolipoma, a histological variant of lipoma, mostly affect the buccal mucosa and causes functional and cosmetic disabilities. Hence, accurate histopathological examination of lipomas is important for a correct treatment plan. This article describes a case of 10 year old girl with fibrolipoma of the buccal mucosa with a relevant review of tumors.